Court-Involved Girls' Perceptions of the Attainability of a Desired Possible Self and Its Connection to Past Adversity and Current Behavior. (October 2017) - Goodson, Marva V.; Morash, Merry
Identity-based motivation theory identifies individuals' perceptions of attainable possible selves as the future-oriented component of self-concept that is a necessary first step in an adolescent's goal setting and motivation for action. This qualitative study analyzed data from interviews with 27 court-involved girls. Girls with histories of sexual assault and emotional abuse were less likely than others to have attainable possible selves. Girls with unattainable possible selves more often broke the law as adults and dropped out of school. Discussion of findings focuses on implications for future research and on potential intervention strategies to promote girls' positive identity development.